PENERAPAN METODE BERNYANYI DALAM PEMBELAJARAN BAHASA ARAB DI KELAS VII MTs YPPTQMH AMBARAWA: Indonesia - Khotimatul Aisyah; Abdul Hamid; Moh. Masrur (STIT Pringsewu, 2022)
Abstract The Singing Method is a vocal act of producing music using sound and adding notes that are continuous in use. Singing is one of the most popular activities, especially for children. So, the singing method that the researcher means is a tactic or a way to achieve the goal by creating a more interesting and fun atmosphere by singing. Singing will make it easier for students to remember and memorize mufrodat in learning Arabic. This study aims to find out the improvement of Arabic mufrodat learning by using the application of the singing method in class VII MTs YPPTQMH Ambarawa and to create a learning atmosphere that is fun and not boring by using the application of the singing method in learning Arabic mufrodat in class VII MTs YPPTQMH Ambarawa. Research methods This research uses qualitative research methods and uses a sample of 20 students in class VII. Based on the results of the study, the seventh grade students of MTs YPPTQMH Ambarawa by using the singing method made the learning atmosphere more interesting and fun. Singing makes it easier for students to remember and memorize mufrodat in learning Arabic. The application of the singing method in Arabic mufrodat learning in class VII MTs YPPTQMH Ambarawa made students more enthusiastic and the role of student involvement during the implementation of the singing method was more dominant. Then communication between students is actively established. In addition, communication between teachers and students becomes communicative and effective. In addition, students' vocabulary mastery increases. Keywords: Singing Method, Arabic Mufrodat.